Implementation of the Problem Based Learning Model to Improving Student Learning Outcomes on the Asmaul Husna Material at SD Negeri Lawa Batu - Wati, Cut Rika; Yulizar, Cut Irma (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to improve student learning outcomes in the Asmaul Husna material through the application of the Problem Based Learning (PBL) learning model. The method used is Classroom Action Research (CAR) which is implemented in two cycles, where each cycle includes the stages of planning, implementation, observation, and reflection. The subjects in this study were 23 sixth grade students of Lawa Batu Public Elementary School. Data collection was carried out through tests, observations, and documentation, then analyzed descriptively quantitatively and qualitatively. The results of the study showed an increase in student learning outcomes, from 35% completeness in the pre-cycle stage to 57% in cycle I, and increased again to 82.6% in cycle II. The application of the PBL model has been proven to be able to increase active student participation, develop critical thinking skills, and deepen understanding of the values of Asmaul Husna. These findings indicate that PBL is an effective learning method in improving learning outcomes, and is in accordance with the demands of learning in the 21st century.